Clinical significance and prognostic impact of the total diameter of enlarged lymph nodes on preoperative multidetector computed tomography in patients with gastric cancer. Issue 11 (November 2015) - Kawaguchi, Tsutomu; Komatsu, Shuhei; Ichikawa, Daisuke; Kosuga, Toshiyuki; Kubota, Takeshi; Okamoto, Kazuma; Konishi, Hirotaka; Shiozaki, Atsushi; Fujiwara, Hitoshi; Otsuji, Eigo
Abstract Background and Aim This study was designed to evaluate the clinical significance and prognostic impact of the total diameter of enlarged lymph nodes (TDL) on preoperative multidetector computed tomography (MDCT) in gastric cancer (GC). Methods Of a total of 480 GC patients between 2005 and 2009, 70 patients with a preoperative diagnosis of nodal metastasis on MDCT were included in this study. All regional lymph nodes showing metastatic involvement were preoperatively counted and measured. Results The TDL was calculated, and using a receiver operating characteristic curve, a cutoff value of 45 mm in the two groups of large TDL (LTDL) and small TDL was found to be appropriate for TDL. No significant differences were observed in clinicopathological features, except for tumor recurrence, between the two groups. Univariate survival analysis revealed that patients with LTDL had a worse prognosis as well as an upper tumor location, deeper tumor depth, and further advanced pathological stage. Multivariable prognostic analysis identified LTDL as an independent worse prognostic factor (P = 0.0128). Conclusions GC patients with the total nodal diameter measuring 45 mm or more on MDCT have a worse prognosis. GC patients with the novel surrogate indicator of worse prognosis for a preoperative imaging diagnosis may have need of multimodal treatment to improve the survival.